Custom exome panel revealed new mutations in MAPK14 and novel mutation in RUNX2 gene in patients with PCOS - Yunus Arikan; Taylan Onat (Scientific Reports)
Abstract Polycystic ovary syndrome (PCOS) is the most common endocrinopathy and is both phenotypically and genotypically heterogeneous. A large number of genetic variants have been found in different genes, so far. Based on the literature, we identified 7 genes and aimed to find new causative variants in these genes. We created a targeted PCOS panel including major genes in the steroidogenezis, WNT, MAPK, and TGFβ pathways and analyzed whole-exome sequencing results. We compared the minor allele frequency (MAF) values of different variants with our results and calculated deleterious scores of newly found variants using various web-based prediction tools and ACMG pathogenicity criteria. We found a novel missense mutation (p.Thr355Ile) in the RUNX2 gene in one patient and heterozygous mutations in the MAPK14 gene (c.306_5delT and c.*8G > T) in another patient with PCOS. Five novel pathogenic moderate (PM2) intronic variants in 4 different genes in total were introduced for the first time. We also decoded 7 genes in patients with PCOS in our cohort. Two more candidate genes (MAPK14 and RUNX2) may be related to PCOS.